Clinically important differences with standard medications used for the breakthrough pain in a hospital at home unit for patients with advanced cancer - Vicente Ruiz-García; Bernardo Valdivieso-Martínez; Elisa Soriano-Melchor; Mónica Albert-Coll; Rosalía Domènech-Clar; Rosa Navarro-Villanueva; Ana Torrego-Giménez; Sylvia Bort-Martí; Nuria Garrido-Rodríguez; Ángela Piqueras-Espallargás (Open Journal of Pain Medicine - Peertechz Publications, 2020)
Background: One out of three cancer patients suffers pain, and half of those patients suffer Breakthrough Pain (BTP). In patients with advanced, metastatic, or terminal disease the number suffering BTP increases to two out of three patients.  BTP is defined as a peak of pain intensity of short duration in patients with stable and acceptable analgesia provided by analgesics given around the clock. Context and purpose of the study: An observational study was performed at the Hospital at Home Unit at the University and Polytechnic Hospital La Fe of Valencia (Spain) to evaluate whether opioid therapy could significantly reduce BTP from baseline within 30 minutes of administration and achieve clinically meaningful differences. Results: In total, 424 BTP episodes were recorded in the study. The incidence of BTP per patient over the study period was 13.7 episodes. There were significant pre-and post-treatment differences in pain intensity as measured on a Visual Analogy Scale (VAS) of 0-100 points/100 (p<0.05). The mean difference of pain between pre- and post-treatment was 35.28 (CI95% 33.55-37.35). The intensity of BTP was highly variable for individual patients, with 70% of the variability being greater than 30 points/100 and 50% being greater than 40 points/100. The most frequent intensity of BTP was moderate. The most frequent time of BPT was the morning/early afternoon. The items related to clinically relevant pain relief after opioid therapy were: level of basal pain, type of basal medication (fentanyl patches), and gender (female). Conclusions: It is recommended to check daily for the appearance of BTP in patients with advanced, metastatic or terminal cancer, especially in Units such as Hospital at Home Units.  We have observed that among opioids drugs, fentanyl patches and slow release morphine, which are the most frequently used opioids for the treatment of BTP, are the ones which achieved a clinically important difference in pain score, independently of the pre-treatment pain severity (mild, moderate or severe) of the patient. The adverse events detected in the present study were few although we estimate that they were probably under-represented. Hence, we recommend that the doctors should ask on daily basis patients suffering from advanced cancer and being treated with opioid drugs for BTP for adverse events and/or insist the patients to report them.